Geometric Phases and The Sagnac Effect: Foundational Aspects and Sensing Applications. Issue 2 (15th January 2022) - Paiva, Ismael L.; Lenny, Rain; Cohen, Eliahu
Abstract: Geometric phase is a key player in many areas of quantum science and technology. In this review article, several foundational aspects of quantum geometric phases and their relations to classical geometric phases are outlined. How the Aharonov–Bohm and Sagnac effects fit into this context is then discussed. Moreover, a concise overview of technological applications of the latter, with special emphasis on gravitational sensing, like in gyroscopes and gravitational wave detectors is presented. Abstract : The notion of geometric phase has been highly influential in quantum science and technology. The current review article outlines the basics and some sensing applications pertaining to this active area of research. A special emphasis is given to two highly popular manifestations of the geometric phase—the Aharonov–Bohm and the Sagnac phases—as well as to their interrelations.